EVALUATIVE LANGUAGE IN THE DISCOURSE OF CEBONG VS KAMPRET (‘TADPOLE VS MICROBATS’) ON TWITTER - Ahmad Fadly (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
As an interactive social media, Twitter gives significat role in creating social systems. Evaluative language was intensively used on the social media. The Cebong vs Kampret issue coloured on Twitter and polarized people. By using data Tweet and Reply from Twitter during 2019 this researcher investigates evaluative language. This research results that Twitter community were very emotionally force and defense on the Cebong vs Kampret issue, depicted from many evaluative languages classified into subsystem attitude. Subsystem graduation was also intensively used in accordance to that issue. It means that Twitter community emphasized on semantic scale in evaluating things and person.